1992
DOI: 10.1001/jama.1992.03490070073045
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 45 Laboratories Participating in a Proficiency Testing Program for Lyme Disease Serology

Abstract: Our results indicate that there is an urgent need for standardization of current testing methodologies. Until a national commitment is made, serological testing for Lyme disease will be of questionable value for the diagnosis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…However, because the study laboratory was located in an area endemic for Lyme disease, we assumed that most patients had potential exposure. Fourth, although interpretation of Lyme disease immunoblots can vary between diagnostic laboratories [25], all but 1 were performed in the same laboratory. Next, our asymptomatic control patients were being evaluated clinically for food or environmental allergies, and we cannot exclude the possibility that the frequency of false-positive Lyme disease serologic results might differ in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the study laboratory was located in an area endemic for Lyme disease, we assumed that most patients had potential exposure. Fourth, although interpretation of Lyme disease immunoblots can vary between diagnostic laboratories [25], all but 1 were performed in the same laboratory. Next, our asymptomatic control patients were being evaluated clinically for food or environmental allergies, and we cannot exclude the possibility that the frequency of false-positive Lyme disease serologic results might differ in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is laborintensive, time-consuming, and subjective, allowing for potential intra-and interlaboratory variation in WB reading and interpretation. Previous studies analyzing the performance of LB serologic tests among testing laboratories have demonstrated significant variation in results, even for more objective methods, such as enzyme immunoassay (2,3,10). Therefore, given the inherent subjectivity in reading and interpreting WBs for diagnosis of LB (i.e., Lyme WBs), one would expect to observe significant variation in WB results, with potentially adverse effects on the laboratory diagnosis of Lyme disease and subsequent patient management decisions.…”
mentioning
confidence: 99%
“…Despite FDA clearance of many of these assays, published proficiency testing studies revealed significant result heterogeneity between the different commercially available kits and, perhaps most worrisome, appreciable intralaboratory variability for duplicate samples. One such study demonstrated that, among the 45 participating laboratories, up to 55% failed to detect antibodies to B. burgdorferi in sera from patients with clinically characterized LD who were seropositive according to a reference IFA (8). Precision was likewise shown to be poor; one laboratory documented a coefficient of variation of more than 120% for a sample tested in triplicate, and another proficiency sample tested across the 45 laboratories had a reproducibility rate of only 27%.…”
Section: Serologic Testing For Lyme Disease: a Historical Perspectivementioning
confidence: 99%